Psychosocial Assistance of Learners in the Limited Face-to-Face Learning Period at Elementary Schools in Southeast Maluku District - Adam Latuconsina; Anasufi Banawi; Sarfa Wasahua; Bahiya Gasam; Enggal Mursalin; Muawana Latuconsina (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Abstract. Community Service Activities (PKM) in the form of mentoring are aimed at, 1) increasing students' reading and numeracy literacy skills, 2) increasing learning motivation and competence in facing face-to-face learning. The methods used during the training were lectures, interactive discussions and mentoring by experts. The results of this PkM activity are, after following the mentoring of students who were shy became more confident. Likewise, students who initially rarely interact or are passive with their friends can finally be more open to playing and learning together.Keywords: quality pursuit program, psychosocial, limited face-to-face learning